THE ROLE OF DOMESTIC INVESTMENT IN POVERTY REDUCTION IN 11 PROVINCES IN JAVA, BALI, NTT, NTB AND MALUKU - Soegoto, Dedi; Wiganepdo, Surjatno; Surdiatno, Herman (Faculty of Economic and Business, University of Pasundan, 2024)
This study aims to investigates the role of domestic investment in reducing poverty in 11 provinces in Indonesia, specifically Java, Bali, East Nusa Tenggara, West Nusa Tenggara, and Maluku. This study employs a quantitative framework, utilizing panel data analysis to investigate trends across selected regions. The findings support region-specific economic strategies that boost growth and reduce poverty by encouraging local investment to reduce poverty and improve living standards. The research highlights the importance of domestic investment in promoting inclusive growth and improving social welfare in Indonesia. This research represents a novel inquiry, as the study of the panel data pool model across 11 provinces provides a wider perspective by emphasizing the importance of domestic investment in promoting inclusive growth and improving social welfare in Indonesia.